1984
DOI: 10.1103/physrevlett.52.1180
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Rotational Brownian Motion of Spheres by NMR

Abstract: We present a new NMR method for the investigation of rotational Brownian motion based on the appearance of dipolar relaxation as the particles rotate. Our experimental results obtained on submicrometer polystyrene spheres in water confirm quantitatively the basic laws of rotational Brownian motion. The effects of hydrodynamic interactions and long-time tails are discussed. PACS numbers: 05.40. +j, 76.60.EsBrownian motion, discovered by R. Brown in 1828, refers to the random movement of small objects like polle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The time dependence of the Hamiltonian during a simple echo measurement gives rise to an echo decay envelope which depends on the quadrupole broadening. More rapid rotational motion has been observed by Esteve et al [7] who investigated the effects of rotational Brownian motion of polystyrene spheres and showed that the resulting nuclear dipole relaxation provides a means to study that motion. Tycko [8] investigated very fast rotation (1-4 kHz) for a pure NQR measurement and observed a spectral splitting associated with Berry's phase.…”
Section: Introductionmentioning
confidence: 87%
“…The time dependence of the Hamiltonian during a simple echo measurement gives rise to an echo decay envelope which depends on the quadrupole broadening. More rapid rotational motion has been observed by Esteve et al [7] who investigated the effects of rotational Brownian motion of polystyrene spheres and showed that the resulting nuclear dipole relaxation provides a means to study that motion. Tycko [8] investigated very fast rotation (1-4 kHz) for a pure NQR measurement and observed a spectral splitting associated with Berry's phase.…”
Section: Introductionmentioning
confidence: 87%
“…An alternative approach for the detection of Brownian relaxation is nuclear magnetic resonance, since the relaxation time for nuclear spins is modified by the rotational motion of the particles [12]. In addition to using intrinsic anisotropies, it is also possible to add anisotropy artificially.…”
Section: Sensing Applications Utilizing Rotational Brownian Motionmentioning
confidence: 99%
“…Ensemble methods such as depolarized dynamic light scattering or fluorescence correlation spectroscopy also require optical or physical anisotropy (Berne & Pecora, 1975;Pieper & Enderlein, 2011;Rogers et al, 2012). NMR can measure the rotation of isotropic ensembles but only at longer timescales (Esteve et al, 1984). The resolution of most optical techniques is of the order of 1 , still far larger than the rotational motion of particles in a colloidal gel.…”
Section: Introductionmentioning
confidence: 99%